Inferring Accounting Information from Corporate Financing Choices: An Examination of Security Issuances in the Banking Industry - BISHOP, MARGUERITE L.; LYS, THOMAS Z. (Contemporary Accounting Research, 2001)
This study examines the impact of regulatory capital and several of its determinants (i.e., earnings, loan loss provisions, charge-offs and growth) on bank managers' financing decisions and investors' interpretations of those decisions. The analysis is related to two streams of research. We add to the corporate finance literature that seeks to explain the market's reaction to security issuances by developing and testing a refined set of predictions of the demand for debt and equity capital using a sample of capital-regulated firms (banks). We extend the accounting literature that links regulatory capital-management decisions with bank performance by examining whether investors infer that performance. We find that bank managers' financing choices reflect their private information regarding the levels of regulatory capital, earnings, and charge-offs in the issuance year. We document a negative market reaction to capital-increasing issuances and a positive reaction to capital-decreasing issuances. A cross-sectional analysis of that market reaction indicates that investors infer managers' expectations of earnings in the issuance year.